INTEGRATED TRAINING IN SPORTS GAMES - LEUCIUC Florin-Valentin; NAWARECKI Dariusz (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Sports training is the process which aims at improving athletes' performance, in order to obtain an optimal physical shape for competitions. Achieving this goal requires simultaneous action on all factors for obtaining a good shape. The fundamental objective of integrated training is to create conditions as close to those of competitions. It was found that there are "preferential connections" and that not everything can be integrated or rather, the integration of training should follow a few basic ideas.